Modern pollen assemblages near the arctic tree line, Mackenzie Delta region, Northwest Territories - Ritchie, J. C. (Canadian Journal of Botany, 1974)
Samples of surficial lake sediment and of moss polsters from 39 sites in the forest-tundra transitional area immediately east of the Mackenzie Delta, Northwest Territories, were investigated palynologically. Lake sediment samples within the forest and tundra regional vegetation zones are constant in pollen frequencies, but forest–tundra sites are very variable. Forest site spectra are composed of just over 50% arboreal types (spruce, 25–30%; birch, 30%), with 30–40% alder pollen. Tundra spectra have 60–70% non-arboreal types, and 10–15% each of alder and spruce. Forest–tundra values are variable, generally lying between the forest and tundra proportions. Polster samples show as much variability within as between regions, because of local effects. Polster samples indicate local community composition with the regional pollen rain variably masked by the local elements.